2015
DOI: 10.1186/s13046-015-0221-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming: the emerging concept and associated therapeutic strategies

Abstract: Tumor tissue is composed of cancer cells and surrounding stromal cells with diverse genetic/epigenetic backgrounds, a situation known as intra-tumoral heterogeneity. Cancer cells are surrounded by a totally different microenvironment than that of normal cells; consequently, tumor cells must exhibit rapidly adaptive responses to hypoxia and hypo-nutrient conditions. This phenomenon of changes of tumor cellular bioenergetics, called “metabolic reprogramming”, has been recognized as one of 10 hallmarks of cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
459
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(469 citation statements)
references
References 88 publications
7
459
0
3
Order By: Relevance
“…There is an emerging school of thought that most ovarian cancer cells may utilize either an increased glycolysis or OXPHOS and that such flexibility confers a higher level of 'cellular fitness' 19,26,41 . This concept has also been observed and defined in other studies 50 . Our work also demonstrated that the 2 chemoresistant ovarian cancer cell lines (C200 and PEO4) 51,52 exhibited a high metabolically active phenotype as compared to their respective sensitive counterparts (A2780 and PEO1).…”
Section: Discussionsupporting
confidence: 51%
“…There is an emerging school of thought that most ovarian cancer cells may utilize either an increased glycolysis or OXPHOS and that such flexibility confers a higher level of 'cellular fitness' 19,26,41 . This concept has also been observed and defined in other studies 50 . Our work also demonstrated that the 2 chemoresistant ovarian cancer cell lines (C200 and PEO4) 51,52 exhibited a high metabolically active phenotype as compared to their respective sensitive counterparts (A2780 and PEO1).…”
Section: Discussionsupporting
confidence: 51%
“…The brain possesses unique metabolic characteristics with respect to glucose availability, such as metabolic coupling between astrocytes and neurons, commonly referred to as the "lactate shuttle." In this scenario, lactate secreted by astrocytes is taken up by neurons to fuel OXPHOS-dependent metabolism (2). Thus, as a consequence of the lactate shuttle, available glucose concentrations are variable and may be growth limiting for brain metastases.…”
Section: Metabolic Adaptation Of Disseminated Cancer Cells To Uniquementioning
confidence: 99%
“…This metabolic symbiosis may be controlled by the differential expression of distinct lactate transporters such as the monocarboxylate transporters, MCT1 and MCT4 (56). Hypoxic/ glycolytic cancer cells express high level of MCT4 that functions as a major lactate exporter, whereas oxygenated/aerobic cells express MCT1, which promotes lactate uptake (2).…”
Section: Metabolic Heterogeneity Within Tumorsmentioning
confidence: 99%
See 2 more Smart Citations